Gambaran Tingkat Pendidikan dan Tinggi Badan Orangtua Balita Stunting Usia 24-59 Bulan - Putri, Nelvi; Nurlinawati, Nurlinawati; Mawarti, Indah (Jurnal Ilmiah Ners Indonesia, 2021)
Stunting has a large impact on the growth and development of children and also the economy of Indonesia in  the future. Stunted toddlers will  generally experience obstacles in cognitive and motor development and also have a greater risk for suffering from non- communicable diseases such as diabetes, obesity, and heart disease in adulthood. Parent's level of education and height are the main determinants of stunting. Therefore, the researcher wants to see an overview of the level of education and stunting of parents of stunting toddlers aged 24-59 months in the working area of the Puskesmas Siulak Mukai, Kerinci Regency. This type of research is descriptive research. In determining the number of samples in this study using a total sampling technique that is all parents who have stunting toddlers aged 24-59 months in the working area of the Puskesmas Siulak Mukai Kabupaten Kerinci used as samples with a total sample of 42 stunting toddlers, sampling using the purposive sampling method. Analysis of the data used in this study is univariate analysis. The results  showed  that  the  level of  education of  high  school fathers equivalent was 42.9%, the level of education of high school fathers as much as 40.5%, father's height was 55% more than the height of short fathers by 45%, high short maternal body as much as 59.5%. The level of education of parents of high school/equivalent and low maternal height can cause children to grow stunting.